Development and Validation of E-Books Based on Socio-Scientific Issues to Improve The Argumentation Skills of High School Students - Khasanah, Minnathul; Purwianingsih, Widi; Supriatno, Bambang (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to develop and analyze the validity of the e-book on environmental pollution based on socio-scientific issues to improve students' argumentation skills. The development of the e-book uses the ADDIE design (Analysis, Design, Development, Implementation, and Evaluation), but this research has only reached the development stage (Development/D). This study used a qualitative descriptive analysis using a validation sheet instrument in the form of a questionnaire by two experts: material experts and technology/application experts. Data analysis technique using Content Validity Ratio (CVR). The validation results of material experts got a score of 98.38% in the very feasible category, while the application/technology expert for evaluating the application of content and language feasibility, respectively, got a score of 85.94% and 81.58% in the very feasible category. Based on the assessment results of the two validators, the e-book on environmental pollution based on socio-scientific issues was declared valid and suitable for use in the learning process. The conceptual implication of this study is that environmental pollution e-books based on socio-scientific issues can facilitate students in developing argumentation skills. As for the practical implications, the e-book can be used as an innovation as a Biology learning resource that makes it easier for students to learn independently and streamlines the delivery of material in learning activities in the classroom for teachers.